2007
DOI: 10.1111/j.1095-8649.2007.01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile sockeye salmon distribution, size, condition and diet during years with warm and cool spring sea temperatures along the eastern Bering Sea shelf

Abstract: Interannual variations in distribution, size, indices of feeding and condition of juvenile Bristol Bay sockeye salmon Oncorhynchus nerka collected in August to September (2000–2003) during Bering–Aleutian Salmon International Surveys were examined to test possible mechanisms influencing their early marine growth and survival. Juvenile sockeye salmon were mainly distributed within the southern region of the eastern Bering Sea, south of 57°0′ N during 2000 and 2001 and farther offshore, south of 58°0′ N during 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…It was not surprising to find that warmer summers, in general, corresponded to improved productivity for sockeye salmon populations from this region of Alaska. This supports previous research which has found that warmer SSTs during the early marine life stage correspond with greater survival (Mueter et al , 2002; Martinson et al , 2009) and growth (Rogers & Ruggerone, 1993; Farley et al , 2007), and that warmer lake temperatures lead to increased growth during freshwater life stages (Schindler et al , 2005; Rich et al , 2009), which can be related to subsequent survival in the marine environment (Koenings et al , 1993). However, the difference in sensitivity by rearing lake was unexpected.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It was not surprising to find that warmer summers, in general, corresponded to improved productivity for sockeye salmon populations from this region of Alaska. This supports previous research which has found that warmer SSTs during the early marine life stage correspond with greater survival (Mueter et al , 2002; Martinson et al , 2009) and growth (Rogers & Ruggerone, 1993; Farley et al , 2007), and that warmer lake temperatures lead to increased growth during freshwater life stages (Schindler et al , 2005; Rich et al , 2009), which can be related to subsequent survival in the marine environment (Koenings et al , 1993). However, the difference in sensitivity by rearing lake was unexpected.…”
Section: Discussionsupporting
confidence: 90%
“…Here, only coarse metrics of ocean thermal conditions or general climate indices (i.e., PDO) were used as potential environmental drivers. More precise mapping of salmon migration patterns in the ocean relative to the spatial and temporal variation in environmental conditions they experience in this phase of their life (Farley et al , 2007) may greatly improve the ability of statistical models to detect the effects of marine conditions on salmon population productivity. However, at present, such data simply do not exist over the time period considered in this study, or at the scale of individual populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the relationship between fish size and their stable isotopes suggests that larger fish may forage in habitat further offshore than their smaller counterparts; this is corroborated by high seas data (e.g. Farley et al 2007). …”
Section: Stable Isotopes and Fish Sizesupporting
confidence: 64%
“…Compensatory growth has been documented in over 20 fish family taxa in laboratory experiments and in natural populations of Atlantic Salmon Salmo salar, Atlantic Herring Clupea harengus, Common Carp Cyprinus carpio, Atlantic Cod Gadus morhua, and Pacific Cutlassfish Trichiurus lepturus (Ali et al 2003). In the eastern Bering Sea, smaller age-1.0 Sockeye Salmon feed at higher rates than larger age-2.0 juvenile Sockeye Salmon (Farley et al 2007b), providing initial evidence for compensatory growth. For Bristol Bay Sockeye Salmon, we hypothesized that smaller and younger smolts at ocean entry would exhibit faster growth during their first year at sea as a means of obtaining a critical size for survival.…”
mentioning
confidence: 99%